Asymmetric Facet Joint Osteoarthritis and Its Relationships to Facet Orientation, Facet Tropism, and Ligamentum Flavum Thickening. Issue 9 (November 2016) - Liu, Hai-xiao; Shen, Yue; Shang, Ping; Ma, Yan-xu; Cheng, Xiao-jie; Xu, Hua-zi
Abstract : Study Design: The degrees of osteoarthritis of the left and right facet joints were evaluated by using computerized tomography among elderly patients with low back or leg pain. Objective: To reveal the phenomenon of asymmetry regarding facet joint osteoarthritis (FJOA) in old patients and establish its relationships to spinal level, facet orientation, facet tropism and ligamentum flavum (LF) thickening. Summary of Background Data: There were few reports regarding left-right asymmetry among severity of FJOA and its relationships to spinal level, facet orientation, facet tropism, and LF thickening remained unclear. Methods: The grade of bilateral FJOA was evaluated using 4-grade scale on computerized tomography images at the L3–4, L4–5, and L5–S1 levels of patients with age ranging from 60 to 80 years. All subjects were divided into 2 groups: symmetric FJOA group (FJOA I–II on both sides or FJOA III–IV on both sides) and asymmetric FJOA group (FJOA I–II on one side and FJOA III–IV on the other side). The relationships of FJOA to spinal level, facet orientation, facet tropism, and LF hypertrophy were evaluated. Results: No association between asymmetric FJOA and spinal level was noted ( P >0.05). In asymmetric FJOA group, significant difference in facet orientation between 2 sides was observed at the L4–5 ( P =0.018) and L5–S1 levels ( P =0.033). Compared with symmetric FJOA, asymmetric FJOA showed significant difference in prevalence of facet tropism at the L5–S1 level ( P <0.001). The LF showed significantly thicker on the side of FJOA III–IV than the side of FJOA I–II at each level in asymmetric FJOA group ( P <0.05). However, no difference was found in thickness between 2 sides in symmetric FJOA group ( P >0.05). Conclusions: Asymmetric FJOA is associated with facet orientation and tropism, but not with spinal level. There is a close relationship between severity of FJOA and LF thickness.